The influence of Carbon Disulfide on Hydroxyl Free Radicals in Phenanthroline Chemiluminescence System - Jian, Le (Tianjin shi lao dong wei sheng yan jiu suo ; Tianjin shi lao dong wei sheng huan jing yi xue hui, 2001)
Objective: To clarify the effects of carbon disulfide (CS2) on hydroxyl free radical (*OH) generation in phenanthroline chemiluminescence system (Phen-system). Methods: The dynamic curve of various concentrations of CS2, the quenching effect of thiourea on chemiluminescence intensity and the influence of CS2 on Phen-system without CuSO4 and Vit C were observed with phenanthroline chemiluminescence system. Results: CS2 could enhance the emission intensity of chemiluminescence and advance the peak time. It had dose-effect relationship between CS2 concentrations (0,10,40,80,120,160 mg/ml) and chemiluminescence peak (r=0.955,R2=0.913，P=0.003), as well as CS2 concentrations and peak time (r=-0.927，R2=0.860，P=0.008). The enhanced chemiluminescence induced by CS2 could be quenched by thiourea but the inhibition rate of it reduced along with the increasing of CS2 concentration (r=-0.816, R2=0.666, P=0.048). When the system were free of CuSO4 and Vit C, CS2 could also induce the emission of luminous intensity. Conclusion: CS2 could induce the generation of hydroxyl free radicals and advance the peak time in Phen-system.